PERBEDAAN EFEKTIFITAS METODE PENDIDIKAN KESEHATAN BASIC LIFE SUPPORT (BLS) AUDIOVISUAL DENGAN DEMONSTRASI TERHADAP KEMAMPUAN LIFE SAVING PADA MAHASISWA ILMU KEPERAWATAN FIK UNIVERSITAS KADIRI - Haryuni, Sri; Sulistyawati, Wiwin (Journal Nursing Care and Biomolecular, 2017)
Cardiovascular disease is the leading cause of death in the world and ischemic heart disease is the most common cause. Emergency conditions (cardiac arrest) can occur anywhere, and to anyone and is an emergency life-threatening condition and requires immediate treatment. Nursing students need to acquire Basic Life Support (BLS) competency as one of the important competencies to provide first aid as one of life saving efforts in patients. BLS health education in nursing students as a candidate for health workers is needed as an effort to improve the live saving ability so that students are able to perform treatment in patients with breath and heart sigh during practice in hospital as well as facing patients with stop breathing and cardiac arrest anywhere. This study aims to determine the differences in the effectiveness of audiovisual Basic Life Support (BLS) health education method with demonstration of live saving ability in students with cardiovascular disease. The method used is quasi experimental, with pretest and posttest design. This research uses Purposive Sampling and divide the respondents into two groups, the audiovisual method group (n = 17) and the demonstration method group (n = 17). Based on the normality test data obtained normal distributed data so that statistical test used is parametric test that is using Paired T Test and Independent T Test. The result of paired t test is obtained pvalue = 0,001, there is difference of life saving before and after training with demonstration method, and pvalue = 0,003, there is difference of live saving ability of student before and after training with audiovisual method. While the test results independent test obtained pvalue = 0.04. This suggests a difference in effectiveness between audiovisual methods and demonstration methods with live saving skills of nursing science students. Based on the results of this study the need for BLS taught in a demonstration in order to further improve the ability of live saving students.